Newly formed and ruptured infectious intracranial aneurysm in few days following first intracranial aneurysm embolization concurrent with middle cerebral artery occlusion: A regrettable case in a baby child - Yunying Yang; Hongtu Ma; Hui Hu; Lusheng Li; Jun Tang (Wiley, 2024)
Abstract Infectious intracranial aneurysm (IIA) and embolic cerebral infarction are well‐known devastating complications of children suffering infective endocarditis. In this report, we describe a successfully embolized IIA concurrent with bilateral middle cerebral artery (MCA) occlusion. Unfortunately, a newly formed IIA located in the contralateral MCA bifurcation ruptured at the seventh day following embolization. A 6‐month‐old female child was admitted to hospital 3 days following acute right limb mobility disorder. An interventional surgery history of congenital heart disease was confirmed. She was immediately started on antibiotic therapy and the computed tomography agiography (CTA) scan showed occlusion of the upper branch of the left MCA. Unfortunately an IIA was located in the distal artery region (DAR) of the ipsilateral anterior cerebral artery. Angiography (digital subtraction angiography) was performed and the DAR IIA was embolized by OnyX‐18 with Magic 1.2 Fr. microcatheter. On the sixth day, magnetic resonance imaging during the hospital stay showed reduced infarction area with no other special sign. Desperately, a major seizure with opisthotonos attacked the baby on the seventh day after embolization. An immediate CTA scan showed massive hematoma in the right basal ganglia and a ruptured bifurcate aneurysm of the right MCA. The parents refused positive treatment and discharged in considering the critical situation. It should be noted that IIA can be fast formed anywhere in cerebral artery and dynamic angio‐image should be performed as supervision.